Globalization, Regionalization and the EU – Japan – U.S. Triad - Adrian Pop (Romanian Journal of European Affairs)
The globalization triggers macro-regionalization, which, in its turn, generates micro-regionalization – the EU being a good example of both. Second, in virtually all scenarios of geopolitical future the recurrent theme is regionalism, which comes in various “shapes and sizes”. That is why maybe we should start to live with the idea of a sort of regionalization by default. Third, how the relationship among the members of the EU-Japan-U.S. triad will look like in future will depend to a large extent on how the American power is going to prevail within the Western world and how it is going to handle the reassertion of countries belonging both to the Western and non-Western worlds. The various possible outcomes entail a plethora of varieties of geopolitical realignments.